Communication strategies on Instagram: A comparative analysis between elite universities - Blanco Sánchez, Tania (2024)
Universities have become brands that use Instagram to attract potential students and generate a sense of community among actual members. This study aims to compare how the best-positioned universities in the world and in Spain, according to the Shanghai ranking, use Instagram as a communication channel. To do this, a mixed descriptive exploratory analysis is chosen, combining qualitative variables, format, discursive intention and function of the visual element; and quantitative, interactions and engagement, to analyze the posts from the first trimester of the 2021/2022 academic year (N = 820). The combined interpretation of both parameters after applying the ANOVA variance test has allowed us to formulate two preliminary publication models. The results reveal heterogeneity in the strategies followed, with differences in format, intention and function of the visual element, in addition to a non-proportional relationship between the frequency of publication and the engagement generated.